Comparing the effects of transcutaneous electrical nerve stimulation and pharmaceutical hyoscine-promethazine compound on duration of second phase of labor - Masoumeh Payandeh; Fatemeh Nahidi; Maliheh Nasiri; Afsaneh Fouladi (Mashhad University of Medical Sciences, 2019)
Introduction: Labor duration is of the factors affecting pregnancy outcomes and damages inflicted on mother and fetus. This study was performed with aim to compare the effects of transcutaneous electrical nerve stimulation (TENS) and pharmaceutical hyoscine - promethazine compound on duration of second phase of labor. Methods: This two-group clinical trial was performed on 84 eligible pregnant women referred to Shahid Chamran Hospital of Kangavar division in 2017. The subjects were placed in two groups of TENS and hyoscine - promethazine (n=42 in each group). In medication group, 20 mg of hyoscine and 25 mg of promethazine were conjointly intramuscularly given at the onset of active phase. In TENS group, TENS device was used with 1 pair of upper electrodes being placed between L1-T10 and 1 pair of lower ones being placed between S2-S4 on both sides of spinal column. Duration of the second phase of labor was assessed in both groups. Data was analyzed by SPSS software (version 17), and Chi-square test, and independent t-test, and paired sample t test. PResults: Mean of contraction duration during the first phase of labor showed no significant difference between two groups (P=0.86). Also, two groups had no significant difference in terms of mean of contraction frequency (P=0.23). Duration of second phase of labor was 26.1  1.96 min in TENS group and 30.7  1.54 min in hyoscine-promethazine group, that no significant difference was observed between two groups (P=0.232). Conclusion: The effect of TENS and Hyoscine-Promethazine combination on duration of second stage of labor was similar.